Notions of Female Authority in Modern Shi’i Thought - Tajali, Mona (Religions, 2011)
The dominant Shi’i gender discourse has undergone major shifts in recent years, resulting in revisions of various jurisprudential rulings on women’s rights and status. Among such shifts, there have been rulings on female authority, particularly women’s right to access political decision-making positions. Despite being a controversial topic that has historically faced much clerical debate and disagreement, in recent years a number of reformist clerics have argued in favor of women’s leadership, which is considered a radical departure from the conventional stance. While there are a number of reasons that have contributed to these modernist clerical views in recent years, I argue that the most significant is women’s demands and mobilization for reform of misogynist Shari‘a-based laws. Through reference to clerical gender discourses unfolding in Iran, a Shi’i state, this work will shed light onto the modernist clerical discourses that resulted from women’s strategic and organized pressuring for enhanced women’s political representation. In this regard, this work will examine the interactions between women’s groups and religious elites, in particular pious women’s efforts to publicize and politicize the issue of female authority and women’s access to leadership positions within the Iranian society, as well as the various types of justifications offered by Shi’i clerics for enhancing women’s political rights. By analyzing the recent clerical reformist discourses, this article identifies two dominant types of justifications used by such clerics in explaining the shift from the conventional stand on the subject of female authority, which are categorized as a contextual rereading and a feminist rereading. This analysis will conclude by evaluating the impact of these different types of clerical responses on the future prospects of reform in the society, especially democratization of religious interpretation.